MODA e MODUS: a comunicação sobre impactos socioambientais da cadeia têxtil como dispositivo para o consumo responsável - Siebert, Fernanda (2024)
Studies indicate that the textile fashion production chain is responsible for several social and environmental impacts across the planet. In this context, consumerism, or consumer society, is identified as the core of the main problems related to the link between fashion and the environment. Although environmental issues are currently being discussed in the media, there is still a gap in studies on critical environmental communication. This exploratory research aimed, therefore, to answer the following main question: how does transparency in communication about the socio environmental impacts generated in the stages of the fashion production chain influence consumer behavior? To answer it, five studies were proposed that complement and interrelate with each other, each dealing with the following aspects: 1) the objective was to seek, through bibliographical research, information on the relationships between fashion and socio-environmental impacts; 2) the objective was to analyze content from two different communication spaces, scientific articles and documentary films, through which data were collected on peculiarities present in environmental narratives; 3) the objective was to provide information about the corporate communication policy of four companies in the clothing sector (Lojas Renner, C&A, Pernambucanas and Riachuelo), through the analysis of sustainability reports; 4) the objective was to gather information about the communication of the Algodão Paraíba Project and the Algodão Project in Agroecological Consortia, based on a case study; 5) the objective was to present qualitative data on consumers' knowledge regarding the textile fashion chain and their respective consumption behavior. The results obtained indicate that: 1) there is a need to create a new awareness regarding consumption; 2) scientific communication is limited to a small portion of the population, while documentaries enable a broader and more accessible discussion; 3) three of the four clothing companies analyzed use the Global Reporting Initiative (GRI) indicator in their reports, which suggests that pressure from investors leads large companies to adopt more environmentally fair practices and policies; 4) the case study demonstrated alternative models to extensive cotton cultivation and highlighted the importance of communication being well articulated for projects of this nature; 5) 114 women responded to the questionnaire, and the data collected showed that 64.9% do not know who makes their clothes, 50% look for good social and environmental practices when buying their clothing, 49.6% look for information through social networks , and 20.4% still have a lot of doubts about the impacts and the means of obtaining information on the subject. In conclusion, it is suggested that transparency in communication can serve as a device for more conscious consumption. It is expected that the data collected in this study will serve as an element that contributes to the development of environmental education and communication policies. Keywords: fashion chain; socio-environmental impacts; environmental communication; environmental communication policy; sustainable communication.